«Le delibere del Collegio Rotale in materia di prassi processuale - De Angelis, Agostino ("Iustitia et iudicium" ; 3, 2010)
The article goes over seven recent decisions of the Rota Romana concerning the trial procedure, which aim to fasten the marriage trial. From these bylaws, concerning general principles of process law, the author derives some interesting considerations about the admittance of a new charge of nullity, the possiblity of closure due to inertia of the parties, the trial ex c. 1682, the short trial, the new proposition of the cause and finally matters concerning the right of appeal